Changes in levels of neuromarkers and cognitive functioning of patients with treatment-resistant schizophrenia - D. . Zubov; M. . Dorofeikova; N. . Petrova; V. . Dorofeykov; M. . Ivanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In this paper we analyze the changes in the blood levels of neuron-specific enolase and S100B protein during combined ECT and pharmacological treatment in patients suffering from treatment-resistant paranoid schizophrenia. Correlations between biomarkers’ serum levels, clinical status and characteristics of cognitive functioning are analyzed.